The family in crisis in late nineteenth-century French fiction - White, Nicholas, 1967- (Cambridge studies in French ;, 1998)
Nicholas White examines how novels represent the crisis in 'family values' in late nineteenth-century France. A wide cultural perspective informs close readings of tales of adultery, illegitimacy, incest and divorce by popular novelists such as Zola and Maupassant as well as by hitherto neglected figures of the period.